(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of the USA participation in the solving of German Question. In the article the reaction of American political circles on the fall down of the Berlin Wall and G. Kohlís 10-points program of reunification of Germany is shown. As it was discovered ñ there were different points of view on the role of the United States in the decision-making process of German question, expressed by the American legislative and executive power representatives, American political scientists as well. During the preparation of the negotiations between Germany and other European countries devoted to the problem of unification of Germany the USA played a significant role and was the creator of formula ìtwo plus fourî. American participation was determined by American national interests in this region which suppose staying stay in Europe as an important player.